STUDENTS’ LEARNING STRATEGIES IN DEVELOPING SPEAKING SKILL AT ENGLISH STUDY PROGRAM ISLAMIC UNIVERSITY OF INDRAGIRI - Sri Erma Purwanti; Fauziah Sudra; Suldania Pratiwi (Program Studi Pendidikan Bahasa Inggris, 2021)
English is a language that is used as a medium of international communication. Unfortunately, the ability of English students at the Islamic University of Indragiri in speaking skills is still considered low. They find it challenging to develop their speaking ability. Therefore they need some strategies to develop their speaking skills. Therefore, this study investigates the learning strategies used by English students to develop their speaking skills. The subjects of this study were 20 English students of semester four at the Islamic University of Indragiri. The research design was descriptive. To collect the data, the researchers administered a questionnaire consisting of 18 statements using the Likert scale. The results from the analysis showed that the students used almost all of the strategies proposed by Oxford (1990). They are cognitive strategies, metacognitive strategies, compensatory strategies, memory-related strategies, effective strategies, and social strategies. In order, the most frequent strategies employed by them were Cognitive Strategies (19%), compensatory strategies (17.75%), and social strategies (16.80%).